INFERTILITAS SEBAGAI ALASAN KHULU’ PERSPEKTIF ULAMA - Arif Marsal (Program Studi Hukum Keluarga Islam, 2018)
In the Islamic Compilation Law in Indonesia that poured out in theconstitution of the Republic of Indonesia number 1 year 1974, thedefinition and the aim of the marriage is stated in one article,which is in chapter 1 sets that the marriage is the bond of the innerbirth between man and woman as a husband and wife, with the aimas to establish a household, a happy and everlasting family basedon the belief of one and only God (KHI, Article 1 Chapter 1).However, the aim of the marriage is not easily to reach in. Thereare many issues come in that caused on an unsuccessful marriage.Furthermore, one of the issues that impact on the failure of themarriage is a husband’s infertility. Moreover, the present of thechild is one of the most noteworthy things in the marriage.Although, having a child is not a compulsory need, it has a bigimpact on the harmony of the household. That point has an impacton the assertion of the wife to lodge a khulu. That matterindubitable enticing to review from the Islamic law perspective.